The predictive value of the TG/HDL index for metabolic syndrome and its components: A cross-sectional study in the PERSIAN Guilan Cohort Population - Amirali Ebrahimi; Farahnaz Joukar; Kourosh Mojtahedi; Saman Maroufizadeh; Soheil Hassanipour; Mohammad Reza Naghipour; Mehrnaz Asgharnezhad; Fariborz Mansour-Ghanaei (Endocrine and Metabolic Science)
Background: Metabolic syndrome (MetS) is a global health concern linked to cardiovascular disease and type 2 diabetes. The triglyceride-to-high-density lipoprotein cholesterol (TG/HDL-C) ratio has emerged as a promising biomarker for MetS due to its strong correlation with insulin resistance and atherogenic dyslipidemia. However, its utility in Middle Eastern populations, particularly in Iran, remains underexplored. Objectives: This study aims to evaluate the association between the TG/HDL-C ratio and MetS in the Guilan Cohort Study (GCS), a population-based survey in northern Iran, and to identify sex-specific cutoff values for MetS prediction. Methods: This cross-sectional analysis included 10,520 adults aged 35–70 from the GCS. Data were collected through structured questionnaires, anthropometric measurements, and biochemical studies. MetS was defined using NCEP ATP-III criteria. Receiver operating characteristic (ROC) curves were used to assess the predictive performance of the TG/HDL-C ratio, and logistic regression models were employed to examine its association with MetS, adjusting for confounders such as age, gender, BMI, and lifestyle factors. Result: The overall prevalence of MetS was 41.8 %, with significant gender disparities (56.3 % in women vs. 25.0 % in men). Central obesity (58.0 %) and dyslipidemia were highly prevalent, particularly among women. The TG/HDL-C ratio demonstrated strong predictive power for MetS, with AUC values of 0.828 for men and 0.832 for women. Sex-specific optimal cutoffs were identified at 3.42 (men) and 2.80 (women), with high sensitivity (83.6 % and 72.2 %) and specificity (69.0 % and 80.9 %). Logistic regression revealed a significant association between the TG/HDL-C ratio and MetS risk, with adjusted odds ratios of 1.49 (men) and 3.02 (women) per unit increase. Conclusion: The TG/HDL-C ratio is a robust and cost-effective biomarker for predicting MetS, particularly in resource-limited settings. The study highlights significant gender disparities in MetS prevalence and risk factors, underscoring the need for gender-tailored interventions. These findings support the integration of the TG/HDL-C ratio into routine clinical practice for early detection and management of MetS. Future research should focus on longitudinal studies and multiethnic validation to further establish the ratio's applicability across diverse populations.